Article RETRACTED due to manipulation by the authors The relationship between the level of physical fitness and the level of depression in elderly age based on gender and marital status - Panggung Sutapa; Kukuh Wahyudin Pratama; Aida Mustapha (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Depression can affect anyone, without discrimination. Therefore, this study aims to determine the relationship between the level of physical fitness and the level of depression in the elderly according to gender and marital status. The sample used for this study consisted of 110 men and women aged 60 to 90 years. The instrument used to assess physical fitness was a modified senior fitness test with 6 test items: 1) 30-second chair stand test, 2) arm curl test (30-second arm curl), 3) 2-minute step test, 4) chair sit and reach test, 5) back scratch test, 6) foot rise and walk test. Level of depression with the Geriatric Depression Scale -15 (GDS -15). For gender and marital status with a questionnaire. The analysis of the data used in this study was done with chi-square tests with acceptance and rejection limits of 5%. The results show that there is a significant relationship between the level of physical fitness and the level of depression with P > 0.05, there is a significant relationship between gender and the level of depression with P > 0.05 and there is a relationship between marital status and the level of depression with P > 0.05.